Knowledge and Antiretroviral Behaviors among HIV/AIDs Patients at HRH Princess Maha Chakri Sirindhorn Medical Center Hospital - Chuemongkon, Wannakon; Dullanee, Thanakorn; Petkhan, Putchong (Vajira Medical Journal : Journal of Urban Medicine, 2016)
Objective: This study aimed to explore knowledge and antiretroviral use behaviors of HIV patients at HRH Princess Maha Chakri Sirindhorn Medical Center Hospital. Methods: A cross-sectional descriptive study was performed in 200 HIV patients who underwent antiretroviral therapy for at least 1 month at HRH Princess Maha Chakri Sirindhorn Medical Center Hospital during June 15, 2014 to January 31, 2015. All participants were 18 years or above. Knowledge and antiretroviral behaviors were evaluated by the knowledge questionnaire of AIDs and antiretroviral therapy and the antiretroviral use behavior questionnaire, respectively. Results: The overall knowledge of AIDs and antiretroviral drugs was classified as intermediate level with the mean score of 29.58 ± 4.93 from total 38 scores and also intermediate level of knowledge in the following domains; AIDs knowledge, antiretroviral agents, knowledge of antiretroviral drugs’ adverse events and management. The mean score of the antiretroviral use behaviors was 96.07 ± 7.87 from total 100 scores. Most participants (79%) had good medication adherence (more than 95%). No relationship was found between the knowledge of AIDs/antiretroviral drugs and the antiretroviral behaviors. Factors affecting antiretroviral behaviors were marital status, education level and adverse events of antiretroviral drugs. Conclusion: The knowledge of AIDs and antiretroviral drugs in HIV patients at HRH Princess Maha Chakri Sirindhorn Medical Center hospital was in the intermediate level. Most of all had good medication adherence.